Reconciling Nuers with Dinkas: A Girardian approach to conflict resolution - Redekop, Vern Neufeld (Religion, 2007)
In the Sudan in the 1990s, violent conflict between the Nuers and the Dinkas, both African tribes in the South of Sudan, included rape, murder, the burning of homes and the abduction of children. This conflict ended through the Wunlit People-to-People Peace Conference, organised in 1999 by the New Sudan Council of Churches, with the support of the Sudan People's Liberation Army. In this essay the conflict and its resolution are interpreted through Rene Girard's theory of the scapegoat mechanism. The essay offers a series of guidelines for successful reconciliation. At the centre of the proceedings was the religious sacrifice of the white bull of Mabior. The resolution of the conflict confirms Girard's theory of sacrificial violence. In the author's view, Girard's theory offers a model for transforming debilitating, imitative and violent behaviours into beneficial and positive ones.